2021
DOI: 10.1186/s12933-021-01391-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the association between TyG index and subclinical atherosclerosis: results from the I-Lan Longitudinal Aging Study

Abstract: Background Insulin resistance (IR) is a known risk factor for cardiovascular disease (CVD) in non-diabetic patients through the association of hyperglycemia or associated metabolic factors. The triglyceride glucose (TyG) index, which was defined by incorporating serum glucose and insulin concentrations, was developed as a surrogate marker of insulin resistance. We aimed to investigate the association between the TyG index and the early phase of subclinical atherosclerosis (SA) between the sexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 46 publications
6
36
1
Order By: Relevance
“…Our data indicate a primary role of diabetes and hypertension in the development of disability in a frail cohort of older adults. Furthermore, consistent with previous investigations [ 64 , 65 ], in our population we observed a robust impact of age (p < 0.001) and admission glycemia (p < 0.001), strongly suggesting that glycemic control is a goal to achieve for avoiding adverse outcomes in this class of patients. Indeed, hyperglycemia worsens a delicate balance in patients with multimorbidity such as frail elders [ 66 68 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data indicate a primary role of diabetes and hypertension in the development of disability in a frail cohort of older adults. Furthermore, consistent with previous investigations [ 64 , 65 ], in our population we observed a robust impact of age (p < 0.001) and admission glycemia (p < 0.001), strongly suggesting that glycemic control is a goal to achieve for avoiding adverse outcomes in this class of patients. Indeed, hyperglycemia worsens a delicate balance in patients with multimorbidity such as frail elders [ 66 68 ].…”
Section: Discussionsupporting
confidence: 92%
“…Two studies showed that patients with elevated TyG index are more likely to develop hypertension [ 22 , 42 ], which was also confirmed in the present research. Moreover, Lu et al found that in a non-diabetic population, higher TyG index was significantly associated with subclinical atherosclerosis in women compared to men [ 43 ]. Further researches have shown that the TyG index is more substantially associated with arterial stiffness, coronary artery calcification, and carotid atherosclerosis than HOMA-IR [ 17 , 20 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high TyG index was independently associated with SA in non-diabetic female, but in NGT male. Regardless of sex, the TyG index is unrelated to the presence of SA in DM patients [ 40 ]. Higher TG and blood pressure had greater impact in both DM patients and those with NGT.…”
Section: Discussionmentioning
confidence: 99%